RELATIONSHIP BETWEEN CONATION AND NURSE ERGONOMIC BEHAVIOR IN PREVENTION OF LOW BACK PAIN - Dinda Nur Fajri Hidayati Bunga; Joni Haryanto; Abu Bakar (Alta Dharma Publisher, 2019)
An awkward posture is the most common and significant factor of Low back pain among nurses. Nurses are often exposed to ergonomic constraints. The study aimed to examine the correlation between the conation with nurse ergonomics behavior in preventing low back pain. This study was an explanatory observational research design using a cross-sectional study. A total of 106 nurses were recruited using a probability sampling method through a simple random sampling technique. Data analysis was performed and presented in descriptive statistics, and significant findings were computed using the chi-square test. The results showed that there is a significant correlation between the conation with nurse ergonomic behavior in preventing low back pain events. Ergonomic behavior is essential for nurses to avoid low back pain. Ergonomic behavior will be formed if a nurse has the intention or conation to do a practice. Intention or conation can be formed from attitudes toward behavior, subjective norms, and perceptions of control. Keywords: Conation, Intention, Ergonomic, Behavior, Low back pain